Pemberdayaan Wanita pada UMKM Berbasis Pertanian di Desa Purba Hinalang Kabupaten Simalungun - Lamria Sidauruk; Patricius Sipayung; Ernitha Panjaitan; Indrawaty Sitepu (Universitas Methodist Indonesia, 2025)
Purba Hinalang Village, Simalungun Regency, is a producer of chilies and tomatoes. However, in terms of welfare, these farmers are generally not economically prosperous. The problem is that horticultural products are perishable and their prices fluctuate in the market, so farmers often experience losses due to very low prices. . In addition to economic losses, rotting chilies and tomatoes in the field can also become a source of contamination for pests and plant diseases. This Community Partnership Program (PKM) aims to provide solutions to farmers' challenges when harvests are abundant and prices are low. The solution offered is mentoring farmers, particularly housewives, in transferring technology for processing chilies and tomatoes into attractively packaged chili floss and tomato sauce, which adds value and boosts farmers' incomes, especially during abundant harvests and low prices. It also has a longer shelf life. Through mentoring and training farmers using a participatory approach within this Community Service Program (PKM), it is hoped that technology transfer will proceed smoothly and eventually produce home-based entrepreneurs who can increase family incomes and thus improve farmers' welfare.